Rational design of protein kinase inhibitors - Yarmoluk, S.M.; Nyporko, A.Yu.; Bdzhola, V.G. (Вiopolymers and Cell, 2013)
Modern methodological approaches to rational design of low molecular weight compounds with specific activity in relation to predetermined biomolecular targets are considered by example of development of high effective protein kinase inhibitors. The application of new computational methods that allow to significantly improve the quality of computational experiments (in, particular, accuracy of low molecular weight compounds activity prediction) without increase of computational and time costs are highlighted. The effectiveness of strategy of rational design is demonstrated by examples of several own investigations devoted to development of new inhibitors that are high effective and selective towards protein kinases CK2, FGFR1 and ASK1.